A numerical and experimental study on the outrigger positioning of a trimaran hull in terms of resistance. (15th February 2020) - Yildiz, Burak; Sener, Bekir; Duman, Suleyman; Datla, Raju
Abstract: Although the trimaran design has gained increasing popularity toward the end of the 20th century, there are a few experimental or numerical data available to aid the designer. In this study, the results of experimental and numerical studies for a high-speed trimaran hull are presented to analyze the resistance and running attitude characteristics. A 1/125 scale model was tested at a single outrigger configuration for a range of speeds up to Froude number of 0.5. A three-dimensional RANS solver code based on the finite volume method was used to simulate the forward motion of the trimaran under two degrees of freedom in calm water. A verification study was conducted to calculate the uncertainties in the computations. Then, nine different outrigger configurations were analyzed using CFD. The wave profile on the center-hull and the wave patterns are provided to show the effect of the interference between the center-hull and outriggers on the calculated resistance. The resistance characteristics of each outrigger configuration are presented. Considerable changes in total resistance are reported in some cases. It is concluded that CFD can be used as a robust, reliable and repeatable method when it comes to examining multiple cases. Highlights: Computational analyses of a trimaran hull form for resistance predictions have been carried out in a wide range of Froude numbers. The numerical simulation results have been verified using the latest solution verification methods and validated with the experiments. Wave interference factors have been calculated to assess the hydrodynamic characteristics of a trimaran hull form for different outrigger positions. Considerable changes in total resistance values have been reported in some longitudinal and lateral positions of side-hulls.